(untitled) (Research, Society and Development, 2022)
This integrative review examines tobacco use related to mental disorders in COVID-19 pandemic and potential interactions involving cytochrome P-450 between tobacco and psychotropic drugs. The five steps of the integrative review development process were considered, namely: elaboration of the guiding question, literature search or sampling, evaluation of data, data analysis, interpretation and presentation of results. A literature search was performed in the Medline and Bireme databases, without language restrictions up to May 2021. Forty-seven articles were found with information on COVID-19, tobacco use and psychiatric illness. Articles were also sought that addressed interactions between major classes of psychotropic drugs and tobacco associated with CYP450 isoforms and genetic polymorphism. Thirty-seven articles were found for interaction among tobacco, cytochrome P450 and antidepressants; 7 including polymorphism; 19 articles involving interaction of tobacco, cytochrome P450 and antipsychotics; 4 including polymorphism; 3 articles describing interaction of tobacco, cytochrome P450 and anxiolytics; 1 including polymorphism; 2 articles regarding interaction of tobacco, cytochrome P450 and mood stabilizers; and 1 including polymorphism. These findings reinforce the importance of recognizing the role of tobacco associated with drug use in mental disorders; indicating the need for monitoring to prevent worsening clinical conditions.